2003
DOI: 10.2303/jecho.1.29
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tissue Doppler Imaging as a New Diagnostic Option in Evaluating Left Ventricular Function

Abstract: In general, pump function and myocardial contractility should be assessed when evaluating left ventricular (LV) systolic function. Ejection fraction obtained from left ventriculography is routinely used as an index of pump function, and the maximum value of the first derivative of LV pressure curve (peak dP/dt) has been used as an index of myocardial contractility. On the other hand, active relaxation of the LV myocardium during early diastole and LV passive filling or compliance during mid-to late diastole ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 98 publications
1
6
0
Order By: Relevance
“…Diastolic performance of the LV has been described conceptually by the following two properties: active relaxation during early diastole and passive stiffness (converse of compliance) during mid-to late-diastole [12][13][14][15][16]. ''Relaxation'' is an active diastolic process of the LV myocardium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diastolic performance of the LV has been described conceptually by the following two properties: active relaxation during early diastole and passive stiffness (converse of compliance) during mid-to late-diastole [12][13][14][15][16]. ''Relaxation'' is an active diastolic process of the LV myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the D-UT directly correlated with the IRT and was inversely correlated to the mitral annular E 0 velocity in all patients within these three groups. The prolongation of IRT and the reduction of E 0 velocity have been recognized to reflect a disturbed relaxation of the LV [15,16]. Thus, the prolongation of D-UT seems to be related to the degree of abnormality in LV relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the AML fibrillation velocity did not correlate with LV size, LV ejection fraction, and E/E 0 . E/E 0 is well recognized as a reliable parameter for predicting the LV filling pressure [19][20][21]. Thus, it was thought that the LV systolic function and LV filling pressure might not affect the magnitude of the AML fibrillation velocity.…”
Section: Discussionmentioning
confidence: 99%
“…In this method only large amplitude echoes of lower Doppler frequencies from tissues such as myocardium or heart muscle are retained and low amplitude echoes of higher Doppler frequencies are suppressed by low pass filter as a result the motion of the tissues can be monitored [1]. Several studies have reported the clinical importance of TDI by comparing systolic and diastolic parameters determined by conventional methods with values obtained with TDI [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%